2021
DOI: 10.3390/atmos12111454
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Gas-Phase Alkylamines at a Coastal Site in the East Mediterranean Atmosphere

Abstract: Atmospheric amines are ubiquitous compounds in the atmosphere, having both natural and anthropogenic origin. Recently, they have been identified as important contributors to new particle formation in the atmosphere, but observations of their atmospheric concentrations are scarce. In the present study we introduce the first systematic long-term observations of gas-phase amines measurements in the East Mediterranean atmosphere. Air samples were collected at the Finokalia monitoring station of the University of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The [DEA] > 2.5 × 10 6 cm –3 (0.1 ppt) can reach an enhancement comparable to HIO 2 in IA-induced nucleation. The detected atmospheric [DEA] and [IA] are higher than 2.5 × 10 6 and 10 6 cm –3 , respectively, e.g., in the East Mediterranean 53 and at Mace Head, 14 where the maximum values of [DEA] and [IA] are 9.4 × 10 8 cm –3 (37.5 ppt) and 10 8 cm –3 , respectively. A recent study based on long-term observations found that [IA] can reach about 2.8 × 10 6 cm –3 in the polluted urban atmosphere in Beijing and Nanjing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The [DEA] > 2.5 × 10 6 cm –3 (0.1 ppt) can reach an enhancement comparable to HIO 2 in IA-induced nucleation. The detected atmospheric [DEA] and [IA] are higher than 2.5 × 10 6 and 10 6 cm –3 , respectively, e.g., in the East Mediterranean 53 and at Mace Head, 14 where the maximum values of [DEA] and [IA] are 9.4 × 10 8 cm –3 (37.5 ppt) and 10 8 cm –3 , respectively. A recent study based on long-term observations found that [IA] can reach about 2.8 × 10 6 cm –3 in the polluted urban atmosphere in Beijing and Nanjing.…”
Section: Resultsmentioning
confidence: 99%
“…The (IA) 4 (DEA) 3 cluster was set as the boundary cluster and allowed to contribute to the cluster formation rate (see details in the Supporting Information). The [IA] and [DEA] were set to 10 5 , 10 6 , 10 7 , and 10 8 cm –3 , ,, and 2.5 × 10 5 , 2.5 × 10 6 , 2.5 × 10 7 , 2.5 × 10 8 , and 5 × 10 8 cm –3 , respectively, corresponding to their atmospheric concentration ranges. Similar to a previous study, the setting values of [IA] are the initial concentrations of the IA monomer.…”
Section: Methodsmentioning
confidence: 99%
“…Ethylamine (EA) is a volatile organic compound (VOC) that is emitted into the atmosphere from a wide range of sources including animal husbandry, marine organisms, automobiles, sewage, and coal and biomass combustion. As a VOC, EA contributes to atmospheric particles via new particle formation by acid–base reactions, , gas-phase oxidation product condensation, cloud condensation nuclei (CCN) activity, displacement reaction of ammonium from particles, , and aging of the pre-existing acidic particles . EA is one of the most abundant short-chain aliphatic amines in atmospheric particles, dominant among C1–C3 aliphatic primary amines in PM2.5 with concentrations up to 100 ng/m 3 . , …”
Section: Introductionmentioning
confidence: 99%